Fractionation and Antibacterial Evaluation of the Surface Compounds from the Leaves of Combretum zeyheri on Selected Pathogenic Bacteria - Monica Manyawi; Winnie Yevai Mozirandi; Dexter Tagwireyi; Stanley Mukanganyama (The Scientific World Journal)
Combretum zeyheri is traditionally used for the treatment of many infections, including bacterial infections. The aim of this study was to fractionate and evaluate antibacterial activity of the crude extract of C. zeyheri, as well as the surface compounds from the leaves of C. zeyheri, in two pathogenic bacteria, Staphylococcus aureus and Pseudomonas aeruginosa. The antibacterial activities of fractions obtained from chromatographic separations were determined using broth microdilution assay on the laboratory and clinical strains of S. aureus and P. aeruginosa. The fractionation of the compounds on the leaf surface yielded 262 fractions. The fractionated compounds with similar TLC profiles were pooled together to yield 47 pools. The extract and pooled fractions CZSC151154, CZSC155160, and CZSC209213 showed significant antibacterial activity with MIC values ranging from 12.5 μg/ml to 100 μg/ml. The clinical strain of S. aureus had MIC greater than 100 μg/ml for CZSC151154 and CZSC155160. The minimum bactericidal concentration values for these fractions were also in the range of 12.5 μg/ml to 100 μg/ml. The extract and fractions CZSC151154, CZSC155160, and CZSC209213 showed a concentration-dependent inhibition of growth in S. aureus. Analyses of the CZSC209213 pool by LC-MS showed the presence of nine compounds which are (3R,7R)-1,3,7-octanetriol, (-)-tortuosamine, 11-aminoundecanoic acid, 1-piperidinecarboxaldehyde, 3-hydroxy-4-isopropylbenzyl alcohol 3-glucoside, hydroxy-isocaproic acid, oleamide, palmitic amide, phytospingosine, and sphinganine. In conclusion, C. zeyheri leaf surface compounds exhibited antibacterial activity. The crude extract and the pooled fractions showed concentration-dependent inhibition of growth on S. aureus. Results from this study indicate the potential of C. zeyheri as a source of lead compounds that may be further developed into antibacterial drugs.